Perlakuan Akuntansi Aset Fisik Berdasarkan PSAK No.16 (Studi Pada PT Pelindo Marine Service) - Nekat Wahyu Bagus Prakoso; Endang Dwi Retnani (Universitas Pendidikan Ganesha, 2021)
This study aims to present the accounting treatment for physical assets referring to the provisions of PSAK No. 16. To achieve these objectives, this study uses a descriptive approach. Data obtained from the finance staff of PT PMS. Based on the results of interviews and various existing documents, this study concludes that PT PMS in determining the characteristics of fixed assets is in accordance with PSAK No. 16.Meanwhile, related to the measurement of the time to recognize fixed assets and the measurement after the recognition of fixed assets is in accordance with PSAK No. 2018. The depreciation method for fixed assets is the straight-line method. Finally, PT PMS has also disclosed important matters related to assets in its financial statements. In general, this study concludes that PT PMS has carried out records well, in accordance with PSAK No. 16 starting from paragraphs 73 to 77